Cost Effectiveness of the Chronic Disease Self-Management Program: Implications for Community-Based Organizations - Rashmita eBasu; Marcia G Ory; Samuel D Towne; Matthew Lee eSmith; Angie eHochhalter; SangNam eAhn (Frontiers Media S.A., 2015)
.